ANALISIS KEPATUHAN CREW PESAWAT MILITER TERHADAP PROSEDUR KESELAMATAN PENERBANGAN DI PUSAT PENERBANGAN SEMARANG - Oktaviani Lety Rani; Ekawati Ekawati; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Aviation safety is a condition that formed as the result of the right and neatly organized flight operations based on the right operation procedures and technical feasibility of the structure and infrastructure along with supporting flight. Helicopter Bell 42 EP with serial number HA 5171 crashed on March 2016 in Poso, Central Sulawesi caused by the failure of flight safety procedures. Flight safety procedures are the responsibility of the crew that must be carried on the flight activity This study aimed to analyze the compliance of military air crew to flight safety procedures. This research used descriptive method with indepth interview approach and observation. Key informants in this study contain of 5 people and 3 people as informants triangulation. The results showed the crew has a good knowledge of flight safety procedures. The attitude of the crew of the flight safety procedures is a very important thing, but the delivery of safety demo to all the passengers is uneven. Tools foe safety are available both inside and outside the plane such as flight manual, live vest, life craft, fire extinguisher, emergency doors, safety belt, glass breaking tool or an ax, and first aid kit. Training for flight crew are safety meeting, night flight training, flight emergency, and practice exams. Control with koba (routine investigation for checking things to endanger aircraft condition) has not been implemented to its fullest. Reward and punishment is given in accordance with the implementation of safety procedures. Flight center parties need to create a safety demo procedure and increase the control of the implementation of flight safety procedures.